Exploration of Mother’s Perception of Toddlers About Stunting: Qualitative Study - Filia Sofiani Ikasari; Iis Pusparina; Fir'ad Setya Nugraha; Ahmad Rizqo Abdillah; Cut Ika Anugrah Kirana; Muhammad Wirandi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Stunting is a significant health issue in Southeast Asia, commonly resulting from chronic malnutrition. Mothers play a crucial role in their children’s growth, development, and stunting prevention. Perceptions shape maternal attitudes and behaviors, influencing care for toddlers. This study aims to explore mothers’ perceptions of stunting in the Martapura 1 Health Center work area Methods: A qualitative study with a descriptive phenomenological approach was conducted. Sixteen mothers of stunted toddlers were selected using purposive sampling. Data were collected through observation, interviews, documentation, and audio recordings. Ethical approval was obtained from the Health Research Ethics Commission of the Stikes Intan Martapura. Results: Five themes emerged regarding mothers' perceptions of stunting: Definition of Stunting: Mothers associated stunting with genetic conditions, malnutrition, underweight, short stature, stunted growth and small body size; Causes of Stunting: Perceptions included many factors, malnutrition, cultural beliefs like "buyu" (a local term), and adequate food intake; Symptoms of Stunting: Mothers identified underweight, short stature, delayed development, small body size, and frequent illness; Prevention of Stunting: Properly fed, regular meal schedules, milk provision, attending posyandu (community health services), and provide vitamins; Handling of Stunting: Mothers mentioned consulting healthcare providers, providing nutritious food, improving dietary patterns, providing vitamins, and ensuring adequate sleep. Conclusion: The study provides insights into maternal perceptions of stunting, covering definitions, causes, symptoms, prevention, and management. The study highlights the influence of sociocultural beliefs on maternal perceptions of stunting, which may contribute to misunderstandings and ineffective prevention strategies. Findings emphasize the need for culturally tailored health education to correct misconceptions and promote evidence-based stunting prevention practices. Strengthening community engagement and healthcare interventions is crucial for enhancing maternal awareness and ensuring the successful implementation of stunting prevention programs. Future research should explore broader populations to capture diverse sociocultural perspectives and their impact on child health.